2019
DOI: 10.1097/hco.0000000000000637
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity of HER2-targeted therapies

Abstract: Purpose of review-Cardiotoxicity is a well recognized adverse effect of human epidermal growth factor receptor 2 (HER2)-targeted therapies. The goal of this review is to highlight recent studies that have advanced our knowledge of the diagnosis, prevention, and management of cardiotoxicity associated with HER2-targeted agents. Recent findings-Several clinical risk factors for cardiotoxicity associated with HER2-targeted therapies have been identified including age, low-baseline left ventricular ejection fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 68 publications
3
47
0
Order By: Relevance
“…A number of studies have shown that global longitudinal strain (GLS) can be used as a predictor of cardiotoxicity and can detect early declines in ventricular mechanics prior to an overt reduction in LVEF (El-Sherbeny et al, 2019;Arciniegas Calle et al, 2018;Potter and Marwick, 2018). In clinical practice, GLS can also help reconcile the significance of asymptomatic fluctuations in LVEF, which occur during serial imaging (Robert et al, 2019). However, it is regrettable that there is still a lack of studies that have evaluated the effect of enalapril on GLS.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that global longitudinal strain (GLS) can be used as a predictor of cardiotoxicity and can detect early declines in ventricular mechanics prior to an overt reduction in LVEF (El-Sherbeny et al, 2019;Arciniegas Calle et al, 2018;Potter and Marwick, 2018). In clinical practice, GLS can also help reconcile the significance of asymptomatic fluctuations in LVEF, which occur during serial imaging (Robert et al, 2019). However, it is regrettable that there is still a lack of studies that have evaluated the effect of enalapril on GLS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a fatal instance of cardiac arrest occurred in a patient with no prior history of heart disease and in whom other reasons related to cardiac arrest were not identi ed. Cardiac arrest as a secondary event is not typical of the recognized cardiotoxicity observed during treatment with HER2-targeted therapies, which manifests as decreased left ventricular ejection fraction and/or symptomatic heart failure dysfunction [10]. The etiology of the cardiac arrest event within the current study was unclear, however causal relationship to TAS0728 could not be excluded due to the temporal association observed.…”
Section: Discussionmentioning
confidence: 68%
“…Overall the reported toxicity profile lapatinib was similar to that of pertuzumab plus trastuzumab [73]. Interestingly, while cardio-toxicity is a well recognized adverse effect of HER2-targeted therapies, adverse cardiac events were not reported in patients with BTC treated with pertuzumab plus trastuzumab or lapatinib in clinical trial [72,73,89].…”
Section: Her2 Targeted Therapiesmentioning
confidence: 72%